Chewing lice of wild birds in Iran: new data and a checklist of avian louse species reported in Iran - Bahiraei, Zahra; Sazmand, Alireza; Khedri, Javad; Babaei, Mohammad; Moeinifard, Erfan; Dik, Bilal (Frontiers in Veterinary Science, 2024)
Between September 2019 and December 2023, a total of 612 wild birds representing 16 orders, 33 families, 60 genera, and 78 species from nine provinces of Iran with different climates namely Hamedan (n = 54), Sistan-va-Baluchestan (n = 372), Kerman (n = 73), South Khorasan (n = 52), Mazandaran (n = 7), Chaharmahal-va-Bakhtiari (n = 2), Gilan (n = 2), Golestan (n = 18), North Khorasan (n = 9), and Razavi Khorasan (n = 23) were examined for chewing lice infestation. Naked eye examination revealed that 58 birds (9.5%) were infested with at least one chewing louse species. Collected lice specimens belonged to 28 species from the families Philopteridae, Menoponidae and Laemobothriidae including Strigiphilus strigis (n = 55, 15.6%), Falcolipeurus quadripustulatus (n = 41, 11.6%), Craspedorrhynchus platystomus (n = 40, 11.3%), Colpocephalum turbinatum (n = 36, 10.2%), Laemobothrion maximum (n = 25, 7.1%), Nosopon lucidum (n = 20, 5.6%), Degeeriella fulva (n = 18, 5.1%), Colpocephalum eucarenum (n = 16, 4.5%), Laemobothrion vulturis (n = 15, 4.2%), Anaticola crassicornis (n = 13, 3.7%), Craspedorrhynchus aquilinus (n = 9, 2.5%), Degeeriella fusca (n = 7, 2.0%), Aegypoecus trigonoceps (n = 7, 2.0%), Quadraceps obscurus (n = 6, 1.7%), Colpocephalum impressum (n = 6, 1.7%), Trinoton querquedulae (n = 6, 1.7%), Colpocephalum heterosoma (n = 5, 1.4%), Colpocephalum nanum (n = 5, 1.4%), Lunaceps holophaeus (n = 4, 1.1%), Quadraceps spp. (n = 4, 1.1%), Actornithophilus uniseriatus (n = 2, 0.6%), Nosopon chanabense (n = 2, 0.6%), Actornithophilus cornutus (n = 1, 0.3%), Cuclotogaster heterographus (n = 1, 0.3%), Falcolipeurus suturalis (n = 1, 0.3%), Laemobothrion atrum (n = 1, 0.3%), Colpocephalum gypsi (n = 1, 0.3%), and Rallicola cuspidatus (n = 1, 0.3%). All of these species except six, i.e., Trinoton spp., C. aquilinus, L. vulturis, L. maximum, C. impressum, C. turbinatum, and C. heterographus are recorded for the first time from Iran. This study is the largest epidemiological study to date performed in the country. Data reported herein contribute to our knowledge about diversity of avian chewing lice from wild birds in Iran. In this paper, an updated checklist of louse species reported from Iran according to their avian hosts is presented.